Possibilities and Prospects for the Development of Criminalistics - Hrehorowicz, Małgorzata (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The aim of this paper is to present the possibilities and prospects for the development of modern criminalistics. Discussion of this matter is of importance due to the observa-tion that criminalistics has, of late, lost its original form. The new techniques, including forensic analysis and biometrics, for example, are applied in traditional criminalistics. Fields of knowledge such as forensic archeology and forensic entomology play a signifi-cant role in solving common crimes and are also gradually forming part of criminalistics. There are still no effective tools, however, to combat economic crime. This paper presents the research capabilities that academic research institutes have in this field and possible ways to equip the authority conducting the proceedings with algorithms for identify-ing and combating economic crime. The paper is divided into three parts. The first part demonstrates the shortcomings of criminalistics in terms of the fight against economic crime. The second part presents the author’s achievements, such as establishing the types of economic opinions and presenting typical traces of economic crime. The third part presents the possibilities for further development of criminalistics.